Design basics : Book one - Fullmer, Donna, ....- (New York : Fairchild, 2012)
Design Basics familiarizes students with the fundamental elements and principles of design, offering them a vocabulary with which to understand and discuss interiors and architecture. Using well-articulated definitions and clear, highly-visual examples, this full-color book will expand students' appreciation of design and help them get started creating their own spaces.
Keywords: Interior decoration; Interior decoration -- Terminology